IMPROVING YOUNGER ADULTS' ATTITUDES TOWARD OLDER ADULTS: THE POTENTIAL OF A MULTI-MEDIA ARTISTIC INSTALLATION. (11th November 2018) - Madrigal, C; Fick, D; Mogle, J; Hill, N; Whitaker, E; Belser, A
Abstract: Negative age-based stereotypes are pervasive in society. Younger adults (YA) are most likely to endorse negative age-based stereotypes. Thus, it is imperative to reach YA through innovative means in order to challenge negative stereotypes. The purpose of this study was to measure and describe YA experiences with and perceptions of a cross-generational, multi-media artistic installation. Changes were examined in YA (n=35; mean:19.37 years old; 94% female; 82% Caucasian) attitudes toward aging and older adults pre-viewing, post-viewing, and one-month post-viewing the installation. Data collected included measures on attitudes toward older adults and aging, analyzed using mixed modeling. Semi-structured interviews focused on participants' subjective experiences were examined via thematic analysis. Both quantitative and qualitative results suggested that the installation improved YA attitudes toward older adults immediately post-viewing and one-month post-viewing. Thematic analysis revealed this improvement might be due to changes in attitudes and anticipated behaviors, reinforcement of positive views of older adults, and transformation of negative views of older adults to more positive views. YA attitudes toward aging did not improve post-viewing or one-month post-viewing. Qualitative results suggest this might be due to pre-existing positive impressions of aging, increased self-awareness of eventual aging, and the affirmation of aging-related fears. Future research is needed to establish whether the installation supports sustained changes in attitudes beyond a one-month time period. This study is an essential step in better understanding the potential for innovative and accessible approaches to address YA attitudes toward older adults with the goal of promoting positive changes in intent and behavior.